2021
DOI: 10.3390/su13094683
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing the Persistent and Transitory Effect of Information and Communication Technology on Environmental Impacts Assessment in Africa: Evidence from Mundlak Specification

Abstract: This study examines the persistent and transitory effects of information and communication technology (ICT) on the environmental impact assessment in Africa. The applied advanced econometrics is based on both the Mundlak and Hausman–Taylor methodology for correcting endogeneity and the feasible generalized least squares (FGLS) method to identify any potential cross-panel correlation. The empirical evidence suggests that an increase in ICT (Internet penetration) has a positive transitory effect on the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Large amounts of electricity will be consumed by devices of information and computer technology (ICT) and technological industrialization (Salahuddin and Alam, 2015). Secondly, the growth of the internet and e-commerce industry could have a crowdingout effect, resulting in the elimination of energy-intensive industries (Shobande, 2021). Digital technologies can contribute to green development by disrupting the geographic boundaries, influencing energy consumption, and optimizing resource integration and environmental decision-making (Dubey et al, 2019;Ren et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Large amounts of electricity will be consumed by devices of information and computer technology (ICT) and technological industrialization (Salahuddin and Alam, 2015). Secondly, the growth of the internet and e-commerce industry could have a crowdingout effect, resulting in the elimination of energy-intensive industries (Shobande, 2021). Digital technologies can contribute to green development by disrupting the geographic boundaries, influencing energy consumption, and optimizing resource integration and environmental decision-making (Dubey et al, 2019;Ren et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The digital economy is an important part of the national economy, and innovation is its essential feature. Digital technology drives knowledge accumulation, information integration, and resource sharing; reduces the cost of knowledge search, storage, processing, and transmission; accumulates innovative resources; and lays the foundation for technological carbon reduction [22]. The use of digital platforms and digital technologies optimizes the allocation of innovation resources [23], reduces the irrational behavior of technology research and development, predicts innovation risks, reduces innovation costs, improves innovation speed and research and development success rates, promotes technological progress through the calculation and analysis of massive information, and drives carbon emissions reduction in the logistics industry through technological linkages and technological spillovers.…”
Section: Mechanism Analysismentioning
confidence: 99%
“…Other scholars believe that the development of information and communication technology will improve environmental quality by reducing greenhouse gas emissions. For example, some studies have shown that the use of the Internet and the increase in Internet penetration will significantly reduce carbon emissions in the long run [ 45 , 46 ]. Increasing investment in information and communication technology infrastructure also has a significant effect on reducing carbon emissions [ 47 ], and the carbon trading platform based on digital information technology can also reduce the cost of carbon trading [ 48 ], and accelerate the reduction of carbon emissions and carbon emission intensity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, intelligent manufacturing workshop can realize carbon emission prediction and low-carbon control based on digital data fusion drive [ 56 ]. On the other hand, “Broadband China” has accelerated the development of China’s telecommunications infrastructure, brought new vitality to economic development under the influence of the epidemic, and may play a role in the green development of all industries [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. At the same time, the network infrastructure brought by “broadband China” plays an important role in accelerating the flow of innovation elements, reducing the spatial barriers of information transmission [ 58 ], promoting the application of innovative technologies [ 59 ], and promoting the realization of regional technological innovation development.…”
Section: Research Hypothesesmentioning
confidence: 99%